Revealing humans’ sensorimotor functions with electrical cortical stimulation - Desmurget, Michel (Philos Trans R Soc Lond B Biol Sci, 2015)
Direct electrical stimulation (DES) of the human brain has been used by neurosurgeons for almost a century. Although this procedure serves only clinical purposes, it generates data that have a great scientific interest. Had DES not been employed, our comprehension of the organization of the sensorimotor systems involved in movement execution, language production, the emergence of action intentionality or the subjective feeling of movement awareness would have been greatly undermined. This does not mean, of course, that DES is a gold standard devoid of limitations and that other approaches are not of primary importance, including electrophysiology, modelling, neuroimaging or psychophysics in patients and healthy subjects. Rather, this indicates that the contribution of DES cannot be restricted, in humans, to the ubiquitous concepts of homunculus and somatotopy. DES is a fundamental tool in our attempt to understand the human brain because it represents a unique method for mapping sensorimotor pathways and interfering with the functioning of localized neural populations during the performance of well-defined behavioural tasks.